Soil Conservation as an Investment in Land - Sverre Grepperud (Statistics Norway, Research Department, 1996)
Most studies on the problem of optimal soil conservation have analyzed soil conservation measures as being time-limited in their effect. This paper extends previous analyses of the soil conservation decision by allowing farmers to make investments in soil conservation structures such as terraces, bundles and ditches. It shows that the main conclusions arrived at in previous studies remain valid. The long-term effects of unanticipated permanent changes in prices and discount rates may go either way independent of whether conservation measures are time-limited or have lasting effects on the soil base.
Keywords: Q12; Q24; 330; Land degradation; investment in structures; comparative statics.